Integrasi Multimedia dalam Pengembangan Pembelajaran Berbasis ADDIE untuk Mendorong Deep Learning di Sekolah Menengah Atas - David Christ Arjo; Yemima El-Roi Pasulu; Siti Handayani; Lisa Gracia Kailola; Dameria Sinaga (Yayasan Darussalam Bengkulu, 2026)
This study aims to explore the integration of multimedia in the development of learning based on the ADDIE model to promote deep learning in senior high schools. This study uses a qualitative approach with a literature review method to analyze relevant journals and studies on multimedia integration, the ADDIE instructional design framework, and its impact on deep learning. The results show that the ADDIE model provides a systematic and structured framework in the development of multimedia learning media that effectively supports students' deep learning process. Multimedia, when designed and implemented through the ADDIE stages—Analysis, Design, Development, Implementation, and Evaluation—encourages student participation, motivation, and understanding by providing interactive and adaptive learning experiences. This integration facilitates meaningful and active learning, which supports the understanding of complex concepts in senior high school education. This study concludes that ADDIE-based multimedia development is a strategic approach in facilitating deep learning, improving instructional quality, and aligning with the needs of modern education.